The influence of social support on the psychological effects of unemployment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Economics at Massey University - Marshall, Andrew (Massey University, 2000)
Over the past two decades the proportion of people suffering long-term unemployment has risen in the developed countries. It is agreed that transitory shocks to aggregate demand initially contributed to the high rates of unemployment but there are divergent views as to why these high rates have persisted. Some suggest that these shocks may influence structural factors on the supply-side of the economy. Darity and Goldsmith (1993; 1996) propose a labour market model in which the deleterious psychological effects of unemployment cause contractions in labour demand and supply to persist thus exacerbating unemployment. The model is outlined and the psychology literature concerning its tenets is reviewed. The literature is reviewed as to whether and how social relationships and support ameliorate the psychological distress associated with unemployment. To determine whether unemployment is psychologically deleterious and whether this may be offset by certain types and sources of social support, an exploratory survey examined a small cross-section of people registered with Work and Income New Zealand (WINZ) as unemployed a year before the study. The respondents included people who remained unemployed throughout the entire period, people who had experienced recurrent spells of unemployment and people who had re-entered paid employment and were employed when surveyed. No difference in psychological wellbeing was found on the basis of employment status but differences were found in perceptions of the availability of different types of support from different sources. Those who were re-employed when they were surveyed gained psychological benefits from support derived from the immediate family and associative relationships (e.g. neighbours, workplace and leisure associates). Emotional and socialising support derived from the immediate family appeared to be particularly psychologically beneficial. The analysis further indicates that psychologically healthy and distressed individuals differ in their perceptions of the availability of support from the immediate family and in the availability of financial support from the overall network.
Keywords: Psychology; Unemployed; Services for